The Effects of Metalinguistic Written Corrective Feedback (WCF) On Language Preparatory School Students` TOEFL Independent Writing Section Score - Saban Kara; Soran Abdulrahman (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This paper examined the impacts of metalinguistic feedback on the TOEFL IBT Independent Writing Section Score of language preparatory school students` over 12 weeks using pre-test and post-test. Experimental group students were exposed to metalinguistic feedback, whereas control group students were exposed to direct feedback in an Academic Writing course. Independent samples t test and paired samples t test were employed to gather quantitative date, while the interview was used to get qualitative data. The results revealed that experimental group students` results were higher than control group ones. It shows that metalinguistic feedback yields better results than direct feedback.